Transcriptome‐Wide Regulation of Key Developmental Pathways in the Mouse Neural Tube by Prenatal Alcohol Exposure. (1st July 2020) - Boschen, Karen E.; Ptacek, Travis S.; Simon, Jeremy M.; Parnell, Scott E.
Abstract : Background: Early gestational alcohol exposure is associated with severe craniofacial and CNS dysmorphologies and behavioral abnormalities during adolescence and adulthood. Alcohol exposure during the formation of the neural tube (gestational day [GD] 8 to 10 in mice; equivalent to4th week of human pregnancy) disrupts development of ventral midline brain structures such as the pituitary, septum, and ventricles. This study identifies transcriptomic changes in the rostroventral neural tube (RVNT), the region of the neural tube that gives rise to the midline structures sensitive to alcohol exposure during neurulation. Methods: Female C57BL/6J mice were administered 2 doses of alcohol (2.9 g/kg) or vehicle 4 hours apart on GD 9.0. The RVNTs of embryos were collected 6 or 24 hours after the first dose and processed for RNA‐seq. Results: Six hours following GD 9.0 alcohol exposure (GD 9.25), over 2, 300 genes in the RVNT were determined to be differentially regulated by alcohol. Enrichment analysis determined that PAE affected pathways related to cell proliferation, p53 signaling, ribosome biogenesis, and immune activation. In addition, over 100 genes involved in primary cilia formation and function and regulation of morphogenic pathways were altered 6 hours after alcohol exposure. The changes to gene expression were largely transient, as only 91 genes identified as differentially regulated by prenatal alcohol at GD 10 (24 hours postexposure). Functionally, the differentially regulated genes at GD 10 were related to organogenesis and cell migration. Conclusions: These data give a comprehensive view of the changing landscape of the embryonic transcriptome networks in regions of the neural tube that give rise to brain structures impacted by a neurulation‐stage alcohol exposure. Identification of gene networks dysregulated by alcohol will help elucidate the pathogenic mechanisms of alcohol's actions. Abstract : Alcohol administered during neurulation causes significant dysregulation of genes in alcohol‐sensitive regions of the neural tube that develop into ventral midline brain structures. Six hours after alcohol, biological pathways related to (i) cellular metabolism, (ii) brain morphology, (iii) ribosome biogenesis, (iv) inflammation, and (v) proliferation are affected. Pathways related to (i) circulatory development and (ii) cell migration and (iii) differentiation are enriched 24 hours after alcohol. The molecular targets of early gestational alcohol exposure elucidate pathogenic mechanisms of subsequent disruptions in brain development. Created with BioRender.